Combined Treatment of Articular Cartilage Defects and Patellar Instability with Autologous Chondrocyte Implantation and Patellar Stabilization - Jacob, Connor C.; Barnes, Ryan H.; Haber, Jordan; Cavendish, Parker A.; Milliron, Eric; Magnussen, Robert A.; Flanigan, David C. (The Journal of Knee Surgery, 2025)
High-grade chondral injuries in the setting of patellar instability are a challenging problem for patients and surgeons. In patients undergoing autologous chondrocyte implantation (ACI) to address cartilage defects, medial patellofemoral ligament (MPFL) reconstruction with or without tibial tubercle osteotomy (TTO) is one option to both treat patellar instability and repair and offload defects. The primary aim of this case series was to describe return to activity, reoperation rates, and instances of recurrent patellar instability after medial patellofemoral ligament reconstruction with ACI with or without TTO. We also discuss reoperation rates among patients with multiple cartilage defects in comparison to those with single cartilage defects. A retrospective chart review from 2010 to 2022 identified patients with patellar instability who underwent concurrent MPFL reconstruction and cartilage restoration at a single academic institution. Data regarding patient demographics, cartilage defect location and size, concomitant procedures, return to activity data, and repeat surgery risk were collected. Review identified 14 patients who underwent cartilage restoration and MPFL reconstruction, including 11 who underwent a concomitant TTO. Clinical follow-up was 2.68 years. All patients returned to activity with a mean time of 13.7 months. There were no instances of graft delamination or persistent symptoms necessitating arthroplasty. One patient underwent a second surgery on the index knee for tibial tubercle hardware removal. Cartilage restoration with patellar stabilization surgery may be effective for addressing high-grade cartilage defects associated with patellar instability.
Keywords: knee; articular cartilage; knee; patella; knee; osteotomy; growth factors; healing enhancement